Funny Bestsellers: Positioning Female Comedian Memoirs in the Book Industry - Corinna Norrick-Rühl (European Journal of American Studies)
Guardian critic Hadley Freeman stated in 2014 that the “book publishing world has, for some time now, become wholly memoirified.” This article will analyze the book industry’s penchant for memoir, focusing on memoirs published by female comedians or comedic actors since Tina Fey’s record-breaking bestseller Bossypants (2011). The article offers a book studies-centered perspective, drawing on quantitative as well as qualitative data. Including a brief case study of the Goodreads Choice Awards in the category “Humor,” this article contributes to a greater understanding of the position of the popular memoir in the book industry.